Fisika Dan Hal yang Menyenangkan Tentangnya - Wiji A. H.M. (Sekolah Pasca Sarjana IAIN Bengkulu, 2020)
Abstract: Physics and the fun things about it. Every year, the PISA (the Program for International Student Assessment) is a worldwide examination held every three years to measure the intelligence of 15-year-old school students in 72 countries. Around 540,000 students from all over the world, including from Indonesia, took the exams conducted by The Organization for Economic Co-operation and Development (OECD) in 2015. The State of Singapore ranks first in the results of the exam which means that Singapore has outstanding students highest in the international education rankings measured by the OECD, with teenagers at the top of the world in mathematics, reading and science. PISA rating is very influential in determining the resilience of human resources in a country. England remains a middle class player - behind countries such as Japan, Estonia, Finland and Vietnam which surprisingly rank high enough to beat several European countries. It can be said that students there are good at mathematics. Indonesian students were also included in the test and were ranked 62 out of 70 countries taking the test. This ranking is better than Brazil, Peru, Tunisia, Fyrom, Kosovo, Algeria, Dominican Republic. Based on the results of the study although many do not like physics, but actually there are still many interesting things about this subject